2006
DOI: 10.2471/blt.05.029207
|View full text |Cite
|
Sign up to set email alerts
|

Danger signs of neonatal illnesses: perceptions of caregivers and health workers in northern India

Abstract: Objective To assess household practices that can affect neonatal health, from the perspective of caregivers and health workers; to identify signs in neonates leading either to recognition of illness or health-care seeking; and to ascertain the proportion of caregivers who recognize the individual items of the integrated management of neonatal and childhood illnesses (IMNCI) programme. Methods The study was carried out in a rural community in Sarojininagar Block, Uttar Pradesh, India, using qualitative and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
7
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 9 publications
10
76
7
4
Order By: Relevance
“…The study done in urban area of New Delhi found that bad child rearing practices were followed in that part of the country [10]. In accordance with the present study finding that the health-care workers lack knowledge on danger signs of newborn, a study done by Awasthi et al in North India, identified that health-care providers could recognize some, but not all, the danger signs in pregnancy as well as in the neonate [14]. If the mothers are informed about the danger signs of the newborn, it will promote timely management of the illnesses and prevent neonatal mortality after home-based deliveries.…”
Section: Pandiamunian and Ishwaryasupporting
confidence: 70%
“…The study done in urban area of New Delhi found that bad child rearing practices were followed in that part of the country [10]. In accordance with the present study finding that the health-care workers lack knowledge on danger signs of newborn, a study done by Awasthi et al in North India, identified that health-care providers could recognize some, but not all, the danger signs in pregnancy as well as in the neonate [14]. If the mothers are informed about the danger signs of the newborn, it will promote timely management of the illnesses and prevent neonatal mortality after home-based deliveries.…”
Section: Pandiamunian and Ishwaryasupporting
confidence: 70%
“…Majority of the mothers were unaware of the general danger signs of newborn; over 50% of the mothers just considered fever, vomiting and jaundice as sign of sickness. Fever and excessive crying was considered to be a general danger sign in a similar study 4 . Majority of care givers in African countries also do not know about signs and symptoms of sepsis, its causes and management 5,6 .…”
Section: Discussionmentioning
confidence: 99%
“…11,[33][34][35] Although respondents in this study recognized illness symptoms, their interpretations of the illnesses, hence, the respondent practices varied considerably. This observation provides an opportunity for local health authorities, researchers and programmers to understand and devise culturally and socially-sensitive educational interventions aimed at reducing perinatal morbidity and mortality.…”
Section: Local Understandings Influence Treatment Practicesmentioning
confidence: 99%